2004
DOI: 10.1021/ja0399066
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Facile Hexatriene Electrocyclizations as a Route to Functionalized Cyclohexenones via Ring Expansion of Cyclobutenones

Abstract: This Communication describes a cascade reaction sequence that leads to highly functionalized cyclohexenones starting from reaction of cyclobutenones with alpha-lithio-alpha,beta-unsaturated sulfones and amides. The hexatriene-cyclohexadiene cyclization steps presumed to be involved in these transformations are among the most facile hexatriene electrocyclizations reported thus far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…7 We realized that the key hexatriene intermediates could alternatively be generated by γ-enolization of the readily available divinyl ketones (1) (Scheme 1). Although generation of extended enolates from R, -unsaturated carbonyl compounds was typically accomplished by reactions with strong bases, 8 we believed that enolization of a complex of 1 with a Lewis acid could be achieved under milder conditions using a tertiary amine base.…”
Section: Chemoselective Cyclizations Of Divinyl Ketones To Cyclohexenmentioning
confidence: 99%
See 1 more Smart Citation
“…7 We realized that the key hexatriene intermediates could alternatively be generated by γ-enolization of the readily available divinyl ketones (1) (Scheme 1). Although generation of extended enolates from R, -unsaturated carbonyl compounds was typically accomplished by reactions with strong bases, 8 we believed that enolization of a complex of 1 with a Lewis acid could be achieved under milder conditions using a tertiary amine base.…”
Section: Chemoselective Cyclizations Of Divinyl Ketones To Cyclohexenmentioning
confidence: 99%
“…13 Cyclization of the camphor-derived enone furnished a single diastereomer of the product (entry 5), whose stereochemistry was consistent with a disrotatory 6π-electrocyclization involving the exo face of the intermediate enolate. 7 The reaction in entry 6 appeared to be more complicated and produced a mixture of two diastereomers in a 78:22 ratio. Apparently, the observed product ratio reflects the thermodynamic stability of the two diastereomers, as a sample of pure trans-15 gives rise to the same ratio of isomers upon standing in chloroform for 3 days at room temperature (Scheme 3).…”
mentioning
confidence: 99%
“…For instance, Spangle and co-workers disclosed that alkyl substituents on either C1 or C3 position could accelerate the cyclization. 10 Sulfonyl substitutions were confirmed as an accelerating factor by Magomedov 11 and Brangänge and respective co-workers. 12 Marvel and coworkers reported that ester groups on C2 and C5 facilitated the cyclization.…”
Section: Special Topic Syn Thesismentioning
confidence: 84%
“…Moreover, the present case of 6π-ERC might be facilitated by a push/pull type mechanism, between the hydrogen bonded enol and the proximal carbonyl (RCO). 27 ChemDraw® calculation of CF 3 -triene intermediate D, applying the extended Hückel method, suggested both large partial positive and negative charges at C-1 and C-6. Carba-6π-electrocyclic ring closure would therefore be favored.…”
Section: Resultsmentioning
confidence: 99%